2018
DOI: 10.15390/eb.2018.7203
|View full text |Cite
|
Sign up to set email alerts
|

What is Value of Reform-oriented in-service Teacher Development Attempts on Inquiry Teaching for Pedagogically Discontented Science Teachers? An Expectancy-value Perspective

Abstract: Bu çalışmada çeşitli düzeylerde pedagojik hoşnutsuzluk yaşayan öğretmenlere odaklanarak reform odaklı hizmet-içi öğretmen eğitimi girişimlerinin değerini araştırdık. Bu amaçla, ilgili durumu detaylı araştırmak için durum çalışması yaklaşımını kullandık, ayrıca orta düzeyde pedagojik hoşnutsuzluk yaşayan 3 fen bilimleri öğretmenini amaçlı örnekleme ile belirledik. Altı farklı veri toplama yolu kullanıldı; dört anket ve iki görüşme. Veri analizi için tümevarımsal nitel veri analizi ve durumlararası karşılaştırma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Research focusing teachers' pedagogical discontentment emphasizes the pedagogical competencies of teachers to successfully facilitate reform-based implementations. Being a relatively new construct, researchers often use pedagogical discontentment as a cognitive tool to explore teachers' receptiveness of reform initiatives (Kahveci et al, 2018;Olitsky, 2015) as well as their openness to areas where they realize their shortcomings to comply with reform and effective instructional outcomes (Koksal and Southerland, 2018;Saka, 2007;Sunal, Hodges, Sunal, 2010).…”
Section: Interaction Of Pedagogical Discontentment and Reformmentioning
confidence: 99%
See 1 more Smart Citation
“…Research focusing teachers' pedagogical discontentment emphasizes the pedagogical competencies of teachers to successfully facilitate reform-based implementations. Being a relatively new construct, researchers often use pedagogical discontentment as a cognitive tool to explore teachers' receptiveness of reform initiatives (Kahveci et al, 2018;Olitsky, 2015) as well as their openness to areas where they realize their shortcomings to comply with reform and effective instructional outcomes (Koksal and Southerland, 2018;Saka, 2007;Sunal, Hodges, Sunal, 2010).…”
Section: Interaction Of Pedagogical Discontentment and Reformmentioning
confidence: 99%
“…Kahveci et al (2017) also found the same link as their quantitative study with 994 science teachers illustrated that the level of pedagogical discontentment that teacher experience has a positive correlation with their attainment to reform suggestions as teachers with high pedagogical discontentment were observed to be more open to reform suggestions compare to their counterparts. Focusing on Turkish science teachers, in a qualitative study Koksal and Southerland (2018) focused on three science teachers with moderate level of pedagogical discontentment and they explored that all science teachers were willing to professional development opportunities.…”
Section: Interaction Of Pedagogical Discontentment and Reformmentioning
confidence: 99%